How COVID-19 impacted people with disabilities: A qualitative study in Delaware - L. Rechner; K.E. Harvey; S. Lancaster; J.A. Horney (Elsevier, 2023)
Objectives: The COVID-19 pandemic created unprecedented challenges for people with disabilities and their caregivers and service providers. An assessment of how the COVID-19 pandemic, and the public health response to it, inequitably impacted the health and well-being of people with disabilities is needed to improve preparedness for future public health emergencies. Interviews were conducted with the goal of documenting the impacts of COVID-19 on community-dwelling individuals in Delaware. Study design: Qualitative interviews using a structured interview guide. Methods: In November and December 2022, interviews were conducted with individuals with disabilities, their caregivers, governmental and non-profit service providers, and elected representatives in Delaware. Interviews focused on obtaining information related to COVID-related threats to maintaining good health, affordable and accessible housing, work, educational opportunities, transportation, and community belonging during the pandemic. Interview transcripts were inductively analyzed. Results: Five themes were identified including changes to, or loss of, home-based medical and other services, changes in daily routines that impacted access to work and education, limits on access to transportation, financial strains and housing issues, and mental health concerns. Conclusions: The COVID-19 pandemic impacted nearly all aspects of the lives of people with disabilities. COVID-19 presented long-term, existential threats to progress made toward independent living, meaningful work, and financial, health, and educational equity for people with disabilities.